CLASSROOM ACTION RESEARCH DESIGN WRITING WORKSHOP AT SMA NEGERI 4 SUNGAI RAYA, KUBU RAYA REGENCY: WORKSHOP PENULISAN DESAIN PENELITIAN TINDAKAN KELAS DI SMA NEGERI 4 SUNGAI RAYA KABUPATEN KUBU RAYA - Dada Suhaida; Hadi Rianto; Saprial Nur; Moad Moad (Indonesian Journal of Engagement, Community Services, Empowerment and Development, 2022)
PkM activities in the form of workshops on writing classroom action research designs through the guidance method at SMA Negeri 4 Sungai Raya, Kubu Raya Regency aim to increase the knowledge and insight of teachers at the high school level about writing classroom action research designs. The method used in this PkM activity is a workshop through the mentoring method. The steps in this PkM activity are: 1) Provide a description of the activity material, which consists of: technical socialization of workshop activities through PTK design guidance, preparation of PTK design themes/titles, procedures and procedures for writing PTK designs, and procedures for processing and conclusion, 2) tricks and strategies for collecting literacy material as citation material in writing. In this activity the PkM team also coordinated with the school regarding teacher readiness in preparing the PTK design. Based on the results of the implementation of the PTK design writing workshop through this guidance method, it received a positive response and was welcomed by the school and teachers. This can be seen from the enthusiasm of the participants. Good PTK and also adds information and techniques to teachers in collecting literacy materials from various sources of online journal articles for teachers for purposes in writing class action research designs so that citation sources can be accounted for